Immediate postpartum anemia and associated factors among women admitted to maternity ward at public hospitals in Harari Regional State, Eastern Ethiopia: A facility-based cross-sectional study - Gizaw Taddesse Abebe; Mohammed Abdurke Kure; Tesfaye Assebe Yadeta; Kedir Teji Roba; Tariku Dingeta Amante (Frontiers Media S.A., 2022)
BackgroundAnemia in the postpartum period remains a considerable public health problem in developing countries, particularly in sub-Saharan Africa. It is the most common indirect cause of maternal morbidity and mortality. It is also a major health problem in women of reproductive age, affecting their quality of life, occupational capacity, lactation, and immunological function. Immediate postpartum anemia has a significant impact on women's quality of life, although its predictors have received little attention in Ethiopia, notably in Harari Regional State. Therefore, this study aimed to determine its magnitude and contributing factors in Eastern Ethiopia.MethodsA facility-based cross-sectional study was conducted from June 1st to August 30th, 2021, among 484 postpartum women admitted to two public hospitals in Harari Regional State, Eastern Ethiopia. Data were collected using a pre-tested, structured interviewer-administered questionnaire. About 2 mL of blood samples were collected and analyzed using the cell-Dyne 1,800 machine. The collected data were entered into Epi-Data version 4.6 and analyzed using SPSS version 25. A multivariable logistic regression analysis was conducted to estimate the effect of independent variables on immediate postpartum anemia. An adjusted odds ratio (AOR) with a 95% confidence interval (CI) was computed to report the presence of the association. Statistical significance was declared at a p-value of < 0.05.ResultsThe overall magnitude of immediate postpartum anemia was 28.1% [95% CI (23.7, 32.1)]. Lack of formal education [AOR: 3.92; 95% CI: (1.85, 8.33)], having antenatal care < 4 visits [AOR: 3.18; 95% CI: (1.53, 6.61)], a history of cesarean delivery [AOR: 3.40; 95% CI: (1.89, 6.10)], a history of maternal blood loss [AOR: 4.78; 95% CI: (2.22, 10.30)], pre-delivery Hgb level < 11 g/dl [AOR:5.46; 95% CI: (3.09,9.67)], and having no iron-folate supplementation [AOR:3.27; 95% CI: (1.31, 8.15)] were factors statistically associated with immediate postpartum anemia.ConclusionsIn this study, nearly one-third of mothers admitted for postpartum care developed anemia within 48 h of giving birth. Women's educational level, frequency of antenatal care, mode of delivery, a history of maternal blood loss, pre-delivery hemoglobin level, and iron-folate supplementation status were identified as immediate postpartum anemia risk factors. Therefore, promoting the benefits of adequate antenatal care and iron-folate supplementation during pregnancy is crucial to avoiding the risks of postpartum anemia.